Determinants of Financing Decisions of Start Up Firms - Karam Pal Narwal; Priyanka Priyanka (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2022)
Having an optimum capital structure is crucial as it leads the company to its better operating performance. This paper examines the key determinants affecting the financing decision of start-up firms with reference to the Delhi NCR region in India by using panel data regression models. The hypotheses are formed based on theories of capital structure and existing literature. The financial information data of a final sample of 29 manufacturing start-up firms are taken into consideration for empirical analysis. The results of this research revealed that firm size, growth opportunities, profitability and liquidity are key factors significantly affecting the capital structure decision of start-up firms in India. The relationship found for firm size, profitability and liquidity supported the hypothesis of pecking order theory while growth variable results supported the hypothesis of trade-off theory. Therefore, the pecking order theory is found to be more applicable here in startup firms in India.